Egyptian Pancratium maritimum L. flowers as a source of anti-Alzheimer's agents - Maha Mohamed Soltan; Ahmed R. Hamed; Mona H. Hetta; Ahmed A. Hussein (Faculty of Pharmacy, Cairo University, 2015)
Elevation of acetylcholinesterase enzyme (AChE) has been reported to be implicated in the etiology of Alzheimer disease (AD). One of the encouraged strategies to fight AD is the plant-derived inhibitors. Amaryllidaceae species are enriched source of alkaloids. The inhibitory properties of roots and bulbs of Pancratium maritimum L. against AChE have been previously reported. In the present study, the flowers of the wild Egyptian P. maritimum were subjected to screening assays to evaluate its potency as inhibitor to AChE. Besides, its antioxidant and cytotoxic properties were also addressed. The acetylcholinesterase inhibitory properties of P. maritimum; total extract and its alkaloid mixture were examined using Ellman's assay. The direct antioxidant examination was carried out using DPPH assay whereas the indirect was monitored by the ability to protect Hepa1c1c7 cells against the induced cytotoxicity produced by tert-butyl hydroperoxide (TBHP). The cytotoxic effect of the total extract and crude alkaloid mixture was evaluated against the human liver hepatoma cell line (HepG2). P. maritimum flowers showed significant inhibitory activity against AChE. The potency of the alkaloid mixture, representing 5.0% of the flowers weight (IC50; 22.02 ± 0.59 μg/ml) was about fourfold of its total extract (IC50; 97.67 ± 4.06 μg/ml). The total extract was able to protect about 33.4% of Hepa1c1c7 against the induced intoxication that carried by TBHP rather than the alkaloid mixture. Weak antioxidant and cytotoxic activities were recorded by both examined samples. Flowers of the Egyptian P. maritimum L. could be an enriched source of AChE inhibitors.